Nano carbon-copper adhesive tape with high soaking property and preparation method of nano carbon-copper adhesive tape

By optimizing the composition and preparation of conductive adhesives and nanocarbon adhesives, combined with the four-layer composite structure design, the shortcomings of nanocarbon copper tape in thermal conductivity, conductivity and adhesive properties are solved, and high thermal homogenization and thin thickness are achieved. Suitable for a variety of electronic devices.

CN119220192AInactive Publication Date: 2024-12-31ANHUI MINGXUN NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411755408.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of adhesive tapes, and particularly discloses a nano carbon-copper adhesive tape with high soaking property and a preparation method thereof.The nano carbon-copper adhesive tape comprises a four-layer composite structure from bottom to top, namely a release layer, a conductive adhesive layer, a copper foil layer and a carbon nano layer, and the thickness of the conductive adhesive layer, the thickness of the copper foil layer and the thickness of the carbon nano layer are 20-40 microns, 10-20 microns and 15-30 microns respectively; wherein the conductive adhesive layer is prepared from a conductive adhesive, and the carbon nano layer is prepared from a nano carbon adhesive; the conductive adhesive and the nanocarbon adhesive both contain polyacrylate pressure-sensitive adhesive, the polyacrylate pressure-sensitive adhesive is high in peel strength and holding power and can provide good bonding performance when being applied to a conductive adhesive layer and a carbon nanolayer, and the heat conductivity and the electric conductivity of the nanocarbon copper adhesive tape are improved by combining optimization of the conductive adhesive and the nanocarbon adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adhesive tapes, and in particular relates to a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. Background Art

[0002] Nanocarbon copper foil tape has good thermal conductivity and heat dissipation performance and is widely used in the field of electronic equipment. With the rapid development of electronic equipment, the demand for nanocarbon copper foil tape is becoming more and more refined. For example, the heat dissipation nanocarbon copper tape disclosed in patent application CN110003812A can meet the demand for ultra-thinness while ensuring heat dissipation when used inside electronic products; for example, the thermal conductive tape disclosed in patent application CN108084910A improves its impedance performance.

[0003] In view of the fact that the demand for electronic equipment in the market tends to be multifunctional, the present invention aims to provide a nano-carbon copper foil tape with good electrical and thermal conductivity. Summary of the invention

[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present invention obtains a nano-carbon copper tape with high thermal uniformity by optimizing the conductive adhesive and the nano-carbon adhesive.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is: The first aspect of the present invention provides a nano-carbon copper tape with high thermal uniformity, wherein the nano-carbon copper tape comprises a four-layer composite structure from bottom to top, namely: a release layer, a conductive adhesive layer, a copper foil layer and a carbon nano layer; The thicknesses of the conductive adhesive layer, copper foil layer and carbon nanolayer are 20-40 μm, 10-20 μm and 15-30 μm respectively; The conductive adhesive layer is made of conductive adhesive, and the carbon nano layer is made of nano-carbon adhesive; The conductive adhesive and the nano-carbon adhesive both contain polyacrylate pressure-sensitive adhesive; In some embodiments, the preparation steps of the polyacrylate pressure-sensitive adhesive are as follows: The reaction monomer and ethyl acetate were heated at 60-70 o C until completely dissolved, add azobisisobutyronitrile-ethyl acetate solution after nitrogen flow for 30-40 min, continue stirring for 6-8 h, after the stirring is completed, rotary evaporate to constant weight to obtain polyacrylate; add active diluent and ethyl acetate to polyacrylate, 70-80 o C and stirred until completely dissolved to obtain the polyacrylate pressure-sensitive adhesive.

[0006] The nano-carbon copper tape provided by the present invention uses copper foil as a substrate, and a conductive adhesive and a nano-carbon adhesive are respectively coated on the surface of the copper foil in a Class 1000 dust-free environment. By optimizing the conductive adhesive and the nano-carbon adhesive, the formed tape has the advantages of high thermal conductivity, high electrical conductivity, and strong adhesion while having the advantages of thin thickness and easy die-cutting. The thermal and electrical conductivity effects of the tape are better than those of graphite sheets produced by traditional processes, and the tape can be widely used in various transformers and various electronic products.

[0007] In some embodiments, the reactive monomers include isooctyl acrylate, butyl acrylate, octadecyl acrylate, and acrylic acid.

[0008] Preferably, based on 100 wt %, the reactive monomers include 75-85 wt % of isooctyl acrylate, 10-18 wt % of butyl acrylate, 3-7 wt % of octadecyl acrylate and 0.5-2.5 wt % of acrylic acid.

[0009] In some embodiments, the reactive diluent comprises tetramethylene acrylate and trimethylolpropane triacrylate.

[0010] Preferably, the mass ratio of tetrahydrofuran acrylate to trimethylolpropane triacrylate is (9-13):1.

[0011] Polyacrylate pressure-sensitive adhesive has an important influence on the bonding performance of the tape. The present invention improves the cohesive energy of the pressure-sensitive adhesive by specifically selecting the reactive monomer, thereby increasing the peel strength and the adhesion retention of the pressure-sensitive adhesive. At the same time, the increase in cohesive energy will lead to a decrease in fluidity, resulting in poor wettability of the adhered object, which makes it difficult to apply the adhesive tape during the production process. For this reason, the present invention adds an active diluent. By specifically selecting the active diluent, the dissolution of polyacrylate is enhanced, the problem of reduced contact area between the pressure-sensitive adhesive and the adhered object caused by the protruding small particles is avoided, and the bonding performance of the polyacrylate pressure-sensitive adhesive is improved.

[0012] In some embodiments, the conductive adhesive is prepared as follows: S1, dissolving 4,4'-dihydroxybiphenyl and anhydrous sodium carbonate in 2-butanone, then adding 11-bromo-1-undecanol, stirring at 50-60°C for 8-12h, after stirring, suction filtering, washing, rotary evaporation to constant weight and then recrystallization to obtain reactant a1; S2, stirring 4-hydroxycyclooctene, succinic anhydride, 4-dimethylaminopyridine and toluene at 110-120° C. for 15-20 h under nitrogen protection, extracting the organic phase after the stirring, concentrating and drying the organic phase, then dissolving it in anhydrous ethanol, and then precipitating it in ice water to obtain reactant a2; S3, stirring reactant a1, reactant a2, 4-dimethylaminopyridine and dichloromethane until dissolved, then adding dicyclohexylcarbodiimide-dichloromethane solution and stirring for 20-25h at -5-5°C under argon protection, after the stirring, rotary evaporation to constant weight, recrystallization, to obtain a nucleating agent; S4. Add nickel powder, a nucleating agent and toluene diisocyanate to the polyacrylate pressure-sensitive adhesive and stir for 40 to 60 minutes to obtain the conductive adhesive.

[0013] In some embodiments, in step S1, the molar ratio of the 4,4'-dihydroxybiphenyl, anhydrous sodium carbonate and 11-bromo-1-undecanol is 1:(2.0-2.4):(1.0-1.4).

[0014] In some embodiments, in step S2, the molar ratio of 4-hydroxycyclooctene to succinic anhydride is 1:(0.9-1.0).

[0015] In some embodiments, in step S4, the nucleating agent accounts for 10-18% of the total mass of the conductive adhesive.

[0016] The nucleating agent used in the conductive adhesive provided by the present invention brings good high temperature shrinkage performance, can further improve the cohesive energy of the conductive adhesive, and increase the holding force. In addition, the present invention avoids phase separation between the nucleating agent and the polyacrylate by specifically selecting the amount of the nucleating agent, thereby ensuring that the cohesive energy of the conductive adhesive is effectively improved.

[0017] At the same time, the conductive adhesive of the present invention also has good thermal conductivity, which is due to the electrical conductivity and thermal conductivity of the nickel powder itself on the one hand; on the other hand, the nucleating agent has an ordered arrangement of rigid rod-shaped macromolecular chains, which makes the intrinsic thermal conductivity of the conductive adhesive in a specific direction significantly better than that of ordinary amorphous polymers. The conductive adhesive containing rigid elements can construct a phonon transmission interconnection network based on a microscopic ordered structure through the ordered orientation of the complete polymer network and the nucleating agent, thereby ensuring high thermal conductivity. In addition, the conductive adhesive of the present invention also has improved conductivity after adding the nucleating agent, which may be due to the fact that the chain segments in the conductive adhesive present nematic crystals, and this arrangement helps to effectively transfer charges, thereby improving the overall conductivity of the material.

[0018] In some embodiments, the preparation steps of the nano-carbon adhesive are as follows: B1. Ultrasonicate GO in a potassium hydroxide solution with a concentration of 5-7 mol / L for 1-2 h, then adjust the pH to 8-9 with 0.4-0.8 mol / L hydrochloric acid, then add butyl bromide and tetraoctylammonium bromide, stir at 90-100 ° C for 2-3 h, cool to room temperature, filter, wash, and vacuum dry to obtain alkylated graphene; B2. Dispersing the alkylated graphene with DMF to obtain a dispersion with a concentration of 12-18 mg / mL, adding polyacrylate pressure-sensitive adhesive and a photoinitiator, and vortexing for 20-40 minutes to obtain the nano-carbon adhesive.

[0019] The present invention selects GO as the carbon material in the nano-carbon adhesive, and after being mixed and cured with the polyacrylate pressure-sensitive adhesive, a heat conduction path is formed through a sheet structure, and the GO is modified by alkylation, thereby reducing the thermal resistance of the GO / polyacrylate pressure-sensitive adhesive interface and improving the thermal conductivity. On the one hand, the interaction force between the alkylated GO surface and the polyacrylate pressure-sensitive adhesive is enhanced, reducing the phonon scattering and thermal resistance at the interface; on the other hand, the alkylated GO surface is more likely to be physically entangled with the polyacrylate molecular chain to form a tighter interface structure, which helps to increase the density at the interface, thereby reducing the interface thermal resistance.

[0020] In some embodiments, in step B1, the GO sheet thickness is ≥5 μm.

[0021] In some embodiments, in step B1, the molar ratio of butyl bromide to tetraoctylammonium bromide is 1:(0.007-0.013).

[0022] In some embodiments, in step B2, the mass ratio of the modified graphene to the polyacrylate pressure-sensitive adhesive is 1:(3-6).

[0023] The present invention ensures the integrity of the heat conduction path by controlling the size of the GO sheets and the mass ratio of the modified graphene to the polyacrylate pressure-sensitive adhesive.

[0024] A second aspect of the present invention provides a method for preparing a nano-carbon copper tape with high thermal uniformity, which specifically comprises the following steps: (1) Apply nanocarbon adhesive to one side of the copper foil layer, 50~60 o C for 5-8 min and then photocured to form a carbon nanolayer; (2) Apply conductive adhesive to the other side of the copper foil layer, 60~80 o C for 5-10 minutes to form a conductive adhesive layer; (3) A release layer is attached to the conductive adhesive layer and rolled up to obtain the nano-carbon copper tape with high thermal uniformity.

[0025] In some embodiments, in step (1), the light curing wavelength is 390-420 nm, the curing speed is 0.4-0.6 m / min, and the light intensity is 190-210 mW / cm 2 .

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention uses copper foil as a substrate, and respectively coats a conductive adhesive and a nano-carbon adhesive on the surface of the copper foil. By optimizing the conductive adhesive and the nano-carbon adhesive, a nano-carbon copper tape with high thermal uniformity is obtained. The tape has the advantages of thin thickness and easy die-cutting while achieving high thermal conductivity, high electrical conductivity, and strong adhesion. It can be widely used in various transformers and various electronic products.

[0028] 2. The present invention improves the cohesive energy of the polyacrylate pressure-sensitive adhesive by specifically selecting the reactive monomers thereof, thereby increasing the peel strength and the adhesion retention of the pressure-sensitive adhesive; and by adding an active diluent to enhance the dissolution of the polyacrylate, the problem of reduced fluidity due to the increase in cohesive energy, such as poor wettability of the adhered object and difficulty in coating, is alleviated, thereby improving the bonding performance of the polyacrylate pressure-sensitive adhesive.

[0029] 3. The conductive adhesive provided by the present invention has good electrical and thermal conductivity. The main raw materials include polyacrylate pressure-sensitive adhesive, nickel powder, nucleating agent and toluene diisocyanate, wherein the nickel powder itself has excellent electrical and thermal conductivity; the nucleating agent brings good high-temperature shrinkage performance, which can further improve the cohesive energy of the conductive adhesive, thereby increasing the holding force, and the orderly arrangement of the rigid rod-shaped macromolecular chains of the nucleating agent can make the intrinsic thermal conductivity of the conductive adhesive in a specific direction significantly better than that of ordinary amorphous polymers. At the same time, the addition of the nucleating agent is conducive to the nematic crystallization of the chain segments in the conductive adhesive. This arrangement contributes to the effective transmission of charges, thereby improving the overall conductivity of the material.

[0030] 4. The present invention reduces the thermal resistance of the GO / polyacrylate pressure-sensitive adhesive interface and improves the thermal conductivity by alkylating GO. DETAILED DESCRIPTION

[0031] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Without departing from the gist or scope of the present invention, other combinations and various improvements within the concept of the present invention may be performed. It is worth noting that the following post-processing steps such as "washing", "rotary evaporation" and "recrystallization" are conventional operations in the art, and those skilled in the art may select them according to actual conditions.

[0032] In order to facilitate those skilled in the art to implement the present invention, some raw materials and manufacturers of the embodiments are described as follows: The GO sheet thickness is 10-20 μm and was purchased from Changzhou Sixth Element Materials Technology Co., Ltd., model SE2431.

[0033] Preparation Example 1 The preparation steps of polyacrylate pressure-sensitive adhesive A are as follows: 100 g of reaction monomers (calculated as 100 wt %, the reaction monomers include 80 wt % isooctyl acrylate, 13 wt % butyl acrylate, 5 wt % octadecyl acrylate and 2 wt % acrylic acid) and 90 g of ethyl acetate were stirred at 65 °C for 2 h. o C until completely dissolved, and after nitrogen flow for 40 min, 100 g of 10 wt% azobisisobutyronitrile-ethyl acetate solution was added, and stirring was continued for 7 h. After the stirring was completed, rotary evaporation was performed to constant weight to obtain polyacrylate; 60 g of active diluent (55 g of tetrahydrofuran acrylate, 5 g of trimethylolpropane triacrylate) and 20 g of ethyl acetate were added to 40 g of polyacrylate, and 75 o C and stirred until completely dissolved to obtain polyacrylate pressure-sensitive adhesive A.

[0034] Preparation Example 2 The preparation steps of polyacrylate pressure-sensitive adhesive B are as follows: 100 g of reaction monomers (calculated as 100 wt %, the reaction monomers include 80 wt % isooctyl acrylate, 13 wt % butyl acrylate, 5 wt % octadecyl acrylate and 2 wt % acrylic acid) and 90 g of ethyl acetate were stirred at 65 °C for 2 h. o C until completely dissolved, and after nitrogen flow for 40 min, 100 g of 10 wt% azobisisobutyronitrile-ethyl acetate solution was added, and stirring was continued for 7 h. After the stirring was completed, rotary evaporation was performed to constant weight to obtain polyacrylate; 80 g of ethyl acetate was added to 40 g of polyacrylate, and 75 o C and stirred until completely dissolved to obtain polyacrylate pressure-sensitive adhesive B.

[0035] Preparation Example 3 The preparation steps of polyacrylate pressure-sensitive adhesive C are as follows: The difference between this preparation example and preparation example 1 is that, based on 100 wt %, the reaction monomers include 80 wt % of isooctyl acrylate, 13 wt % of butyl acrylate, and 7 wt % of octadecyl acrylate.

[0036] Preparation Example 4 The preparation steps of polyacrylate pressure-sensitive adhesive D are as follows: The difference between this preparation example and preparation example 1 is that, based on 100 wt %, the reaction monomers include 80 wt % of isooctyl acrylate, 13 wt % of butyl acrylate, and 7 wt % of acrylic acid.

[0037] Preparation Example 5 The preparation steps of conductive adhesive A are as follows: The specific amounts of the solvents "2-butanone", "toluene" and "dichloromethane" in this preparation example can be selected by those skilled in the art according to actual conditions; S1, dissolving 1 mol of 4,4'-dihydroxybiphenyl and 2.2 mol of anhydrous sodium carbonate in 2-butanone, then adding 1.3 mol of 11-bromo-1-undecanol, stirring at 55°C for 10 h, filtering after stirring, washing, rotary evaporating to constant weight, and then recrystallizing to obtain reactant a1; S2, 1 mol of 4-hydroxycyclooctene, 0.95 mol of succinic anhydride, 0.02 mol of 4-dimethylaminopyridine and toluene were stirred at 115° C. for 16 h under nitrogen protection, and the organic phase was extracted after the stirring was completed. The organic phase was concentrated and dried, and then dissolved in anhydrous ethanol, and then precipitated in ice water to obtain reactant a2; S3, 35g of reactant a1, 18g of reactant a2, 1g of 4-dimethylaminopyridine and dichloromethane were stirred until dissolved, then 80g of 50wt% dicyclohexylcarbodiimide-dichloromethane solution was added at 0°C and under argon protection and stirred for 24h, after which the stirring was completed, rotary evaporated to constant weight, and recrystallized to obtain a nucleating agent; S4. Add 80 g of nickel powder, 50 g of nucleating agent and 50 g of toluene diisocyanate to 200 g of polyacrylate pressure-sensitive adhesive A, and stir for 50 minutes to obtain the conductive adhesive A.

[0038] Preparation Example 6 The preparation steps of conductive adhesive B are as follows: The difference between this preparation example and preparation example 5 is that the amount of 4,4'-dihydroxybiphenyl used in step S1 is 1.4 mol.

[0039] Preparation Example 7 The preparation steps of conductive adhesive C are as follows: The difference between this preparation example and preparation example 5 is that the amount of 4,4'-dihydroxybiphenyl used in step S1 is 0.6 mol.

[0040] Preparation Example 8 The preparation steps of conductive adhesive D are as follows: The difference between this preparation example and preparation example 5 is that in step S4, the polyacrylate pressure-sensitive adhesive A is replaced by an equal amount of polyacrylate pressure-sensitive adhesive B.

[0041] Preparation Example 9 The preparation steps of conductive adhesive E are as follows: The difference between this preparation example and preparation example 5 is that in step S4, the polyacrylate pressure-sensitive adhesive A is replaced by an equal amount of polyacrylate pressure-sensitive adhesive C.

[0042] Preparation Example 10 The preparation steps of conductive adhesive F are as follows: The difference between this preparation example and preparation example 5 is that in step S4, the polyacrylate pressure-sensitive adhesive A is replaced by an equal amount of polyacrylate pressure-sensitive adhesive D.

[0043] Preparation Example 11 The preparation steps of nano carbon adhesive A are as follows: B1, 2 g GO was ultrasonicated in 1 L of 6 mol / L potassium hydroxide solution for 1 h, then the pH was adjusted to 8.5 with 0.6 mol / L hydrochloric acid, and then 0.1 mol bromobutyl and 0.01 mol tetraoctylammonium bromide were added, stirred at 95 ° C for 3 h, cooled to room temperature, filtered, washed, and vacuum dried to obtain alkylated graphene; B2. Disperse 10 g of alkylated graphene with DMF to obtain a dispersion with a concentration of 15 mg / mL, add 45 g of polyacrylate pressure-sensitive adhesive A and 1.1 g of photoinitiator TPO, and vortex for 30 min to obtain the nanocarbon adhesive A.

[0044] Preparation Example 12 The preparation steps of nano carbon adhesive B are as follows: 10 g of GO was dispersed in DMF to obtain a dispersion with a concentration of 15 mg / mL, 45 g of polyacrylate pressure-sensitive adhesive A and 1.1 g of photoinitiator TPO were added, and the mixture was vortexed for 30 minutes to obtain the nano-carbon adhesive B.

[0045] Preparation Example 13 The preparation steps of nano carbon adhesive C are as follows: The difference between this preparation example and preparation example 11 is that polyacrylate pressure-sensitive adhesive A is replaced by an equal amount of polyacrylate pressure-sensitive adhesive B.

[0046] Preparation Example 14 The preparation steps of nano-carbon adhesive D are as follows: The difference between this preparation example and preparation example 11 is that polyacrylate pressure-sensitive adhesive A is replaced by an equal amount of polyacrylate pressure-sensitive adhesive C.

[0047] Preparation Example 15 The preparation steps of nano carbon adhesive E are as follows: The difference between this preparation example and preparation example 11 is that polyacrylate pressure-sensitive adhesive A is replaced by an equal amount of polyacrylate pressure-sensitive adhesive D.

[0048] Example 1 A nano-carbon copper tape with high thermal uniformity comprises a four-layer composite structure from bottom to top, namely: a release layer, a conductive adhesive layer, a copper foil layer and a carbon nano layer; The method for preparing the nano-carbon copper tape with high thermal uniformity in this embodiment comprises the following steps: (1) Coat the nanocarbon adhesive A on one side of a copper foil layer with a thickness of 15 μm. o After drying at 400 °C for 7 min, the carbon nanolayer was photocured to form a 22 μm thick carbon nanolayer. The photocuring wavelength was 410 nm, the curing speed was 0.5 m / min, and the light intensity was 200 mW / cm 2 ; (2) Apply conductive adhesive A to the other side of the copper foil layer. o C for 7 min to form a conductive adhesive layer with a thickness of 30 μm; (3) A release layer is attached to the conductive adhesive layer and rolled up to obtain a nano-carbon copper tape with high thermal uniformity.

[0049] Example 2 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the nano-carbon adhesive A is replaced by the nano-carbon adhesive B.

[0050] Example 3 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the nano-carbon adhesive A is replaced by the nano-carbon adhesive C.

[0051] Example 4 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the nano-carbon adhesive A is replaced by the nano-carbon adhesive D.

[0052] Example 5 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation manner is the same as that of Embodiment 1, except that the nano-carbon adhesive A is replaced by the nano-carbon adhesive E.

[0053] Example 6 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the conductive adhesive A is replaced by the conductive adhesive B.

[0054] Example 7 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the conductive adhesive A is replaced by the conductive adhesive C.

[0055] Example 8 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the conductive adhesive A is replaced by the conductive adhesive D.

[0056] Example 9 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the conductive adhesive A is replaced by the conductive adhesive E.

[0057] Example 10 This embodiment provides a nano-carbon copper tape with high thermal uniformity and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the conductive adhesive A is replaced by the conductive adhesive F.

[0058] Performance Testing

[0059] 1. Peel strength Use 180 o The peel strength test method is to test the peel strength of the tape with a width of 25 mm. After the product is attached to the steel plate, it is rolled with the GT-7090 electric rolling roller of the High Speed ​​Rail Technology Co., Ltd. The rolling number is 1 and the roller speed is 5 mm / s.

[0060] 2. Surface resistance Use a multi-function ammeter to measure the surface resistance.

[0061] 3. Thermal conductivity The thermal conductivity was measured using a thermal conductivity tester (LW9389, ASTM 5470).

[0062] The results are shown in Table 1.

[0063] Table 1 Performance test results

[0064] It can be seen from the data in Table 1 that the nanocarbon copper tape in Example 1 has good adhesion, electrical conductivity and thermal conductivity. Compared with Example 1, the GO in the nanocarbon adhesive used in Example 2 is not alkylated, which may reduce the interaction between the GO surface and the polyacrylate pressure-sensitive adhesive, resulting in a decrease in thermal conductivity.

[0065] Compared with Example 1, the polyacrylate pressure-sensitive adhesive in the nano-carbon adhesive used in Example 3 and the conductive adhesive used in Example 8 was prepared without adding active diluent, which reduced the peel strength of the tape and also decreased the electrical and thermal conductivity to a certain extent.

[0066] Compared with Example 1, the amount of 4,4'-dihydroxybiphenyl used in the conductive adhesive used in Examples 6-7 was changed during preparation, which would affect the formation of orderly arranged rigid rod-shaped macromolecular chains by the nucleating agent, thereby reducing thermal conductivity and electrical conductivity. From the changes in the peel strength, surface resistance and thermal conductivity data, it can be seen that changing the reactive monomer used in the polyacrylate pressure-sensitive adhesive will affect its bonding force, and when it is applied to nanocarbon adhesives (Examples 4-5) and conductive adhesives (Examples 9-10), the electrical and thermal conductivity will also decrease.

[0067] The embodiments described above do not impose any form of limitation on the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A nano-carbon copper tape with high thermal uniformity, characterized in that: The nano-carbon copper tape comprises a four-layer composite structure from bottom to top, namely: a release layer, a conductive adhesive layer, a copper foil layer and a carbon nano layer; The thicknesses of the conductive adhesive layer, copper foil layer and carbon nanolayer are 20-40 μm, 10-20 μm and 15-30 μm respectively; The conductive adhesive layer is made of conductive adhesive, and the carbon nano layer is made of nano-carbon adhesive; The conductive adhesive and the nano-carbon adhesive both contain polyacrylate pressure-sensitive adhesive; The preparation steps of the polyacrylate pressure-sensitive adhesive are as follows: The reaction monomer and ethyl acetate were heated at 60-70 o C until completely dissolved, add azobisisobutyronitrile-ethyl acetate solution after nitrogen flow for 30-40 min, continue stirring for 6-8 h, after the stirring is completed, rotary evaporate to constant weight to obtain polyacrylate; add active diluent and ethyl acetate to polyacrylate, 70-80 o C and stirred until completely dissolved to obtain the polyacrylate pressure-sensitive adhesive.

2. The nano-carbon copper tape with high thermal uniformity according to claim 1, characterized in that: The reactive monomers include isooctyl acrylate, butyl acrylate, octadecyl acrylate and acrylic acid.

3. The nano-carbon copper tape with high thermal uniformity according to claim 1, characterized in that: The reactive diluent comprises tetrahydrofuran acrylate and trimethylolpropane triacrylate.

4. The nano-carbon copper tape with high thermal uniformity according to claim 1, characterized in that: The preparation steps of the conductive adhesive are as follows: S1, dissolving 4,4'-dihydroxybiphenyl and anhydrous sodium carbonate in 2-butanone, then adding 11-bromo-1-undecanol, stirring at 50-60°C for 8-12h, after stirring, suction filtering, washing, rotary evaporation to constant weight and then recrystallization to obtain reactant a1; S2, stirring 4-hydroxycyclooctene, succinic anhydride, 4-dimethylaminopyridine and toluene at 110-120° C. for 15-20 h under nitrogen protection, extracting the organic phase after the stirring, concentrating and drying the organic phase, then dissolving it in anhydrous ethanol, and then precipitating it in ice water to obtain reactant a2; S3, stirring reactant a1, reactant a2, 4-dimethylaminopyridine and dichloromethane until dissolved, then adding dicyclohexylcarbodiimide-dichloromethane solution and stirring for 20-25h at -5-5°C under argon protection, after the stirring, rotary evaporation to constant weight, recrystallization, to obtain a nucleating agent; S4. Add nickel powder, a nucleating agent and toluene diisocyanate to the polyacrylate pressure-sensitive adhesive and stir for 40 to 60 minutes to obtain the conductive adhesive.

5. The nano-carbon copper tape with high thermal uniformity according to claim 4, characterized in that: In step S1, the molar ratio of the 4,4'-dihydroxybiphenyl, anhydrous sodium carbonate and 11-bromo-1-undecanol is 1:(2.0-2.4):(1.0-1.4).

6. The nano-carbon copper tape with high thermal uniformity according to claim 4, characterized in that: In step S2, the molar ratio of 4-hydroxycyclooctene to succinic anhydride is 1:(0.9-1.0).

7. The nano-carbon copper tape with high thermal uniformity according to claim 4, characterized in that: In step S4, the nucleating agent accounts for 10-18% of the total mass of the conductive adhesive.

8. The nano-carbon copper tape with high thermal uniformity according to claim 1, characterized in that: The preparation steps of the nano carbon adhesive are as follows: B1. Ultrasonicate GO in a potassium hydroxide solution with a concentration of 5-7 mol / L for 1-2 h, then adjust the pH to 8-9 with 0.4-0.8 mol / L hydrochloric acid, then add butyl bromide and tetraoctylammonium bromide, stir at 90-100°C for 2-3 h, cool to room temperature, filter, wash, and vacuum dry to obtain alkylated graphene; B2. Dispersing the alkylated graphene with DMF to obtain a dispersion with a concentration of 12-18 mg / mL, adding polyacrylate pressure-sensitive adhesive and a photoinitiator, and vortexing for 20-40 minutes to obtain the nano-carbon adhesive.

9. The nano-carbon copper tape with high thermal uniformity according to claim 8, characterized in that: In step B2, the mass ratio of the alkylated graphene to the polyacrylate pressure-sensitive adhesive is 1:(3-6).

10. A method for preparing the nano-carbon copper tape with high thermal uniformity according to any one of claims 1 to 9, characterized in that: The specific preparation steps include: (1) Apply nanocarbon adhesive to one side of the copper foil layer, 50~60 o C for 5-8 min and then light-cured to form a carbon nanolayer; (2) Apply conductive adhesive to the other side of the copper foil layer, 60~80 o C for 5-10 minutes to form a conductive adhesive layer; (3) A release layer is attached to the conductive adhesive layer and rolled up to obtain the nano-carbon copper tape with high thermal uniformity.